Zero Likes – Symbolic interactions and need satisfaction online. (March 2018) - Reich, Sabine; Schneider, Frank M.; Heling, Leonie
Abstract: The paper looks at the symbolic interactions on social networking sites, such as Likes on Facebook, and their role in users' sense of social in- or exclusion. In an online experiment, users of Facebook were asked to write a possible status update and then received note about the numbers of hypothetical Likes they received (zero, two, or thirty) and who (close friends or acquaintances) pressed the Like button. Multivariate analysis of variances showed that belongingness and self-esteem needs are threatened when people do not receive Likes. In contrast, more Likes seem to satisfy these needs better. The influence of who gives the Likes is minor compared to the sheer number of Likes. Highlights: Likes are a form of symbolic interaction within social networking sites (SNS). Zero Likes on SNS threaten fundamental needs and affect. Likes from close friends (vs. acquaintances) best satisfy fundamental needs.